Entrepreneurial Skills Training Manual for Smallholder Livestock Keepers (Amharic Version: 2nd Edition) - Ekule, Muluken; Wamatu, Jane (International Center for Agricultural Research in the Dry Areas, 2022)
The overall goal of this manual is to equip smallholder farmers, youth groups, and other community-based organizations with basic concepts of entrepreneurship and business planning knowledge essential for the success of budding entrepreneurs involved in small businesses along the livestock value chain in Ethiopia. The chapters of this manual can be delivered as a complete package or as selected according to the specific training needs of the intended participants.